NOMENCLATURE AND TYPIFICATION OF MUSA SALACCENSIS ZOLL. EX KURZ (MUSACEAE) - J. F. VELDKAMP; LULUT DWI SULISTYANINGSIH (Research Center for Biology, 2015)
VELDKAMP, J. F. & SULISTYANINGSIH, L. D. 2015. Nomenclature and typification of Musa salaccensis Zoll. ex Kurz (Musaceae). Reinwardtia 14(2): 299 - 302. - A nomenclatural history is given for Musa salaccensis (Musaceae) from Java and Sumatra, Indonesia. Previous typifications are rejected and a lectotype is designated here from original material.